P-078 The role of male factor accompanying PGT-A as possible complementary strategies to control miscarriage. (30th June 2022) - Belchin, P; Sanchez, M; Cabello, Y; Gosalvez, J; García, A; Ordóñez, D
Abstract: Study question: Considering maternal influence or management of male factor, should only PGT-A be indicated to reduce miscarriage? Summary answer: The finest cost-effective treatment for each patient to improve ART success, is a good, tailored, and individualized indication for choosing the best IVF technique. What is known already: Advanced maternal age is related with fertility decline, oocyte quality and the increased risk of aneuploid embryos. Aneuploid embryos lead to a reduced implantation potential and higher miscarriage rate. PGT-A is a screening method to determine the chromosomal status of the embryos and it's the most expanded technique used to reduce the miscarriage rates in most clinics. Common sperm capacitation techniques used in IVF laboratories could cause sperm DNA damage, leading to a smaller number of blastocysts obtained per cycle and a higher miscarriage rate. Microfluidics devices or sperm selection centrifugation-free (Swim-up modified techniques) could reduce sperm DNA fragmentation. Study design, size, duration: This is a retrospective study from 2018-2020 including patients using their own oocytes fertilized by ICSI. No major differences on male factor were found between male patients. In all cycles at least one good quality blastocyst was obtained to biopsy on blastocyst stage in cycles with PGT-A or to transfer without PGT-A. Live-Birth Rate (LBR) per cycle is compared and analyzed by the t-Student and X2 test between groups. Participants/materials, setting, methods: A total of 308 cycles were included in this study. Three groups of patients were formed: Group 1: 76 cycles with PGT-A; Group 2: 191 cycles without PGT-A and sperm samples processed by Swim-Up technique; and Group 3: 41 cycles without PGT-A and a centrifugation free sperm selection (IO-Lix) used for ICSI. The main indication for PGT-A was maternal age. No differences between male or other female infertility factors were found between groups. Main results and the role of chance: When we compare the 3 groups, no statistically significant differences were obtained in fertilization rate (79.8%; 73.5%; 72.6%; p = 0.28); development to the blastocyst stage (48.7%; 43.1%; 44.9%; p = 0.11) and pregnancy rate per transfer (48.8%; 45.6%; 52.8%; p = 0.55). It seems that PGT-A doesn't affect the viability, or the implantation potential of the biopsied embryos and a special sperm capacitation technique is useful for daily clinical use. If we include only patients with ages >38 years old to avoid age differences, comparing Group 1 (PGT-A) and Group 3 (no-PGT-A and IO-lix) (LBR=19.7% vs 50%), we obtain statistically significant differences between both groups (p = 0.01). No differences were found between Group 2 (LBR=26.4%; p = 0.25) and the Group 1. To summarize, the female age appears to be the most important factor for IVF success and the PGT-A can help to avoid a miscarriage, however when we compare women with advanced maternal age, the LBR is increased when PGT-A is non performed, and the sperm DNA is not damaged by the capacitation technique. Why not PGT-A to be complemented with efficient sperm selection? Limitations, reasons for caution: Although sperm selection techniques to decrease sperm DNA damage could reduce miscarriage rates, PGT-A is the only used technique that allows us to ensure that euploid embryos are transferred. Wider implications of the findings: A better understanding of male factor in IVF treatments can reduce miscarriage. Male factor assessment is a cost-effective technique to improve LBR in those patients without a clear indication for PGT-A, (advanced maternal age). Patient must be studied individually, and PGT-A shouldn't be used indiscriminately to ensure a healthy new-born. Trial registration number: Not Applicable